Appointment Logic for the Inaugural Leaders of Newly Established Public Sectors: A Study based on Prefectural Emergency Management Bureaus in China - Guo, Wenbo (International Journal of Social Sciences and Public Administration, 2026)
Throughout China's successive rounds of institutional reform, the establishment of new agencies reflects the developmental characteristics and future directions of the public sector in different periods. The appointment logic for inaugural leaders has emerged as a critical issue. This study analyzes information concerning the inaugural directors of prefectural Emergency Management Bureaus (EMBs) in China. The findings reveal that older male local officials are more likely to be appointed as inaugural EMB directors, with the Han ethnicity constituting the overwhelming majority. In ethnic regions, minority officials are appointed based on local circumstances. To ensure stable management during the initial establishment phase, an overwhelming majority of these inaugural directors are members of the Communist Party of China. To ensure the overall quality of inaugural directors, officials with a bachelor's degree or higher are generally selected, although educational attainment is not the primary determining factor. Officials with relevant prior work experience are more likely to be appointed. Furthermore, due to the urgency of institutional reform and the unique nature of emergency system operations, the tenure of inaugural EMB directors is shorter than the average tenure for directors of pre-existing departments.